A quality assessment methodology for EIE resources available through the internet - Deniz, Derviş Z.; Marzo, Jose L.; Genon-Catalot, Denis; Thiriet, Jean Marc (IEEE Computer Society, 2008)
E-learning has become widely available and accepted by learners either as the main or supplemental facility in their learning activities. A wide range of electronic resources and virtual learning environments are now available over the Internet for use by learners and educators alike. Recent standardisation work has defined learning/sharable content objects at a more fundamental asset level. Further, a number of metadata standards have been developed to help in content aggregation of objects into courseware. This paper presents a quality assessment methodology developed within the EU Socrates EIE-Surveyor Project for evaluating online e-learning resources. The proposed methodology is applied to resources available in the field of Electrical and Information Engineering and some early results are presented. The proposed quality assessment methodology has two main parts: an electronic catalogue (e-Cat) and an evaluation survey (e-Surv) for users of the linked e-resource. The e-Cat serves the purpose of cataloguing e-resources available in the field of Electrical and Information Engineering over the European Internet area and making them available to learners across Europe and beyond. The e-Surv is an e-Cat resource hyperlinked questionnaire comprising evaluation in four main sections: type of users, quality of contents, technical aspects of the resource, overall user satisfaction. E-Surv is designed to allow continuous assessment of the quality of e-resources available within the e-Cat through user surveys. © 2008 IEEE.
19th EAEEIE (European Association for Education in Electrical and Information Engineering) Annual Conference --
Keywords: Computer aided instruction; Learning systems; Quality control; Surveys; Content aggregations; Continuous assessment; Electrical and information engineerings; Electronic resources; Metadata Standards; Quality assessment; Quality of contents; Virtual learning environments; E-learning